1996
DOI: 10.1128/jb.178.7.2150-2153.1996
|View full text |Cite
|
Sign up to set email alerts
|

A CUC triplet confers leucine-dependent regulation of the Bacillus subtilis ilv-leu operon

Abstract: Regulation of the ilv-leu operon probably involves interaction of a tRNA GAG with leader region mRNA. Conversion of a CUC (Leu) triplet located within the leader region to UUC (Phe), CGC (Arg), or UAC (Tyr) converted reporter gene expression to control by corresponding amino acids. Conversion of the CUC triplet to CUU (Leu) decreased expression and disrupted regulation. The results suggested that other tRNAs can substitute for tRNA Leu but that interactions in addition to pairing of the anticodon with the CUC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 15 publications
2
40
0
1
Order By: Relevance
“…The Bacillus subtilis tyrS gene, encoding tyrosyltRNA synthetase, is a member of the T box family of aminoacyl-tRNA synthetase and amino acid biosynthesis genes (Grundy & Henkin, 1993, 1994aHenkin, 1994;Condon et al+, 1996)+ Expression of the genes in this family is dependent on readthrough of a factorindependent transcriptional terminator located in the leader region of the mRNA, upstream of the start of the coding sequence+ Readthrough of the terminator in each gene is stimulated by interaction of the cognate uncharged tRNA with the leader mRNA, resulting in formation of an antiterminator structure that prevents formation of the terminator+ Genetic studies have revealed two positions of base pairing between the tRNA and the leader RNA+ The anticodon of the tRNA pairs with a single codon, designated the specifier sequence, and the acceptor end of the tRNA pairs with a side bulge in the antiterminator (Fig+ 1; Grundy & Henkin, 1993;Grundy et al+, 1994)+ Experiments in which these determinants of the tyrS leader were replaced with those corresponding to a noncognate tRNA demonstrated that these elements are sufficient to direct interaction with certain other tRNAs, albeit at lower efficiency than the interaction with the cognate tRNA (Grundy & Henkin, 1993;Grundy et al+, 1997)+ In other cases, substitutions at the specifier and antiterminator did not result in induction directed by another tRNA+ Similar results have been observed for the ilv-leu, thrS, and valS genes (Putzer et al+, 1995;Marta et al+, 1996;Luo et al+, 1997)+ These results indicate that elements of the tRNA in addition to the anticodon and acceptor end are probably required, and that additional features of the tRNA-leader interaction are likely to be important for efficient readthrough+…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The Bacillus subtilis tyrS gene, encoding tyrosyltRNA synthetase, is a member of the T box family of aminoacyl-tRNA synthetase and amino acid biosynthesis genes (Grundy & Henkin, 1993, 1994aHenkin, 1994;Condon et al+, 1996)+ Expression of the genes in this family is dependent on readthrough of a factorindependent transcriptional terminator located in the leader region of the mRNA, upstream of the start of the coding sequence+ Readthrough of the terminator in each gene is stimulated by interaction of the cognate uncharged tRNA with the leader mRNA, resulting in formation of an antiterminator structure that prevents formation of the terminator+ Genetic studies have revealed two positions of base pairing between the tRNA and the leader RNA+ The anticodon of the tRNA pairs with a single codon, designated the specifier sequence, and the acceptor end of the tRNA pairs with a side bulge in the antiterminator (Fig+ 1; Grundy & Henkin, 1993;Grundy et al+, 1994)+ Experiments in which these determinants of the tyrS leader were replaced with those corresponding to a noncognate tRNA demonstrated that these elements are sufficient to direct interaction with certain other tRNAs, albeit at lower efficiency than the interaction with the cognate tRNA (Grundy & Henkin, 1993;Grundy et al+, 1997)+ In other cases, substitutions at the specifier and antiterminator did not result in induction directed by another tRNA+ Similar results have been observed for the ilv-leu, thrS, and valS genes (Putzer et al+, 1995;Marta et al+, 1996;Luo et al+, 1997)+ These results indicate that elements of the tRNA in addition to the anticodon and acceptor end are probably required, and that additional features of the tRNA-leader interaction are likely to be important for efficient readthrough+…”
Section: Introductionmentioning
confidence: 71%
“…The structure of the acceptor stem can be an important determinant for recognition by the cognate aminoacyltRNA synthetase (McClain et al+, 1999)+ Of the 7 bp in this stem in B. subtilis tRNA Tyr , the only position that differs in E. coli tRNA Tyr is A3-U70 (to U3-A70; Fig+ 2); the G4-C69 and G6-C67 pairings were modified to C4-G69 and C6-G67 in the expression constructs without apparent effect+ To test if base-pair substitutions predicted to destabilize the acceptor stem would affect the ability to direct tyrS readthrough, positions 69-72 were varied in the context of the ⌬Var-U44A construct+ A pool of oligonucleotide cassettes containing all possible substitutions at these positions was used to generate multiple independently derived mutant pools+ After subcloning of the pooled mutants into the tRNA expression cassette, ability to direct expression of a tyrS-lacZ AMB-A222U fusion in B. subtilis was tested+ Only the wild-type sequence was identified in the isolates that effectively promoted tyrS expression+ Several negative isolates were characterized to demonstrate that the appropriate mutants were contained in the pool (Table 2)+ These results indicate that the structure of the acceptor stem is important for tRNA Tyr -directed antitermination+ D loop mutations Garrity and Zahler (1994) identified mutations in the D loop of tRNA Leu GAG that resulted in constitutive expression of the ilv-leu operon, a member of the T box family for which tRNA Leu GAG is predicted to be the effector (Grundy & Henkin, 1994a;Marta et al+, 1996)+ These mutations, which included G-to-A substitutions at the very highly conserved G18 and G19 positions, were postulated to reduce charging efficiency, thereby resulting in elevated ilv-leu expression during growth in the presence of leucine+ Because substitutions at these positions were tolerated in tRNA Leu , all possible substitutions at these positions of tRNA Tyr BGII were tested using an oligonucleotide cassette with a mixture of all 4 nt at these positions, and the pooled mutants were screened for expression of the tyrS-lacZ AMB-A222U fusion+ Thirteen blue isolates from nine independently derived pools were obtained, and DNA sequencing revealed that only the wild-type GG combination was represented+ A number of white isolates were also characterized to ensure that the mutagenesis was successful; 9 of the possible 15 variants were identified in a random sampling of 24 white isolates, indicating that the pools contained the expected sequence variants+ In addition, variants in which the GG sequence was replaced with a single C or by three bases (UCA) were obtained, possibly as the consequence of errors in oligonucleotide synthesis, or misrepair during plasmid propagation+ The G18A allele, which corresponds to tRNA Leu mutant leuG5, was specifically tested in both the BGII and ⌬Var contexts, and no increase in tyrS-lacZ expression was observed (Table 3)+ The G18/G19 mutagenesis was repeated in the context of the COMP variant of tRNA Tyr , to test whether the D stem structure could influence the effect of D loop sequence variation+ Again, the only variants conferring increased tyrS-lacZ expression retained the wild-type GG sequence+ A sample white isolate containing the G18U substitution conferred only background expression (Table 3); this allele also drastically reduced amber suppression (data not shown)+ The failure to obtain efficient tyrS-lacZ expression with mutants of the G18/ G19 sequence indicates that these residues are critical in tRNA Tyr for antitermination, although it is unknown whether this is due to specific ...…”
Section: Acceptor Stemmentioning
confidence: 99%
“…Previous studies have shown that the amino acid specificity of a given T-box system can be synthetically redesigned by mutational changes in the specifier codon (Grundy & Henkin, 1993;Grundy et al, 1997;Luo et al, 1997;Marta et al, 1996;Putzer et al, 1995). Following these leads, we altered the CCU proline-specifier codon in the proBA mRNA leader sequence to a phenylalanine-specific UUC codon, and this change supplanted the original prolinespecific response with a phenylalanine-specific regulatory response ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…3a) functions as the specifier element and confers proline specificity upon the regulation of proBA via the T-box system. Studies with several T-box-regulated genes have revealed that the amino acid specificity of a given T-box system can be altered through mutational changes of the specifier codon (Grundy & Henkin, 1993;Luo et al, 1997;Marta et al, 1996;Putzer et al, 1995). Hence, the redesign of the specificity of a given T-box system by manipulating the putative specifier codon is a genetic approach that can identify a particular codon in the 59-leader region of the transcript as the specifier.…”
Section: Induction Of Proba Transcription Is Sensitively Controlled Bmentioning
confidence: 99%
“…The third branchedchain amino acid gene product, LeuC, was found to be less abundantly expressed by 3-fold in mutant strain in our study. Although it has been known that these gene products were subjected to multiple mechanisms of regulation such as tRNA-mediated transcriptional anti-termination in response to leucine availability (Grandoni et al, 1992;Marta et al, 1996) or catabolite repression (Shivers and Sonenshein, 2005), lower expression of these proteins in mutant strain might have resulted from direct negative regulation of CodY.…”
Section: Metabolic Pathway Proteinsmentioning
confidence: 99%